Single-board microcontrollers applied to biaxial tests for architectural membranes - Beccarelli, Paolo; Martin, Benjamin; Lau, Benson; Chilton, John; Bonardi, Stefano; Maffei, Roberto (2015)
The last decade has been characterised by the progressive development of several biaxial testing equipment and procedures for the mechanical characterisation of coated fabrics. The few standards available in this field led to the development of several testing machines based on different loading principles to reproduce a biaxial stress state in a fabric. The most common approach is based on the symmetrical loading of a cruciform sample by means of four actuators, one on each side. However, other concepts have been successfully applied such as the “floating frame”, where the upper reaction frame is mounted on spherical bearings and is free to move in the plane of the fabric, and the use of rigid square frame with batteries of independent servomotors on each side [6]. Two recent interlaboratory studies confirmed a fairly good correspondence in the values of stiffness obtained by the different laboratories.